2022
DOI: 10.1097/ccm.0000000000005426
|View full text |Cite
|
Sign up to set email alerts
|

Early Neuromuscular Blockade in Moderate-to-Severe Pediatric Acute Respiratory Distress Syndrome

Abstract: The use of neuromuscular blocking agents (NMBAs) in pediatric acute respiratory distress syndrome (PARDS) is common but unsupported by efficacy data. We sought to compare the outcomes between patients with moderate-to-severe PARDS receiving continuous NMBA during the first 48 hours of endotracheal intubation (early NMBA) and those without.DESIGN: Secondary analysis of data from the Randomized Evaluation of Sedation Titration for Respiratory Failure (RESTORE) clinical trial, a pediatric multicenter cluster rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Since PALICC 2015 (1), one small study ( n = 22) found that NMB decreased mean airway pressure, reduced transpulmonary pressure, and did not worsen atelectasis (31). Two small, single-center nonrandomized studies showed a decrease in mean oxygenation index (OI) after continuous NMB in the first 48 hours after initiation of invasive MV (32, 33). The small case-control study performed in a low-resource setting (LRS) showed lower mean OI and lower mortality (13.7% vs 46.7%) compared with case-matched patients not receiving continuous NMB (32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since PALICC 2015 (1), one small study ( n = 22) found that NMB decreased mean airway pressure, reduced transpulmonary pressure, and did not worsen atelectasis (31). Two small, single-center nonrandomized studies showed a decrease in mean oxygenation index (OI) after continuous NMB in the first 48 hours after initiation of invasive MV (32, 33). The small case-control study performed in a low-resource setting (LRS) showed lower mean OI and lower mortality (13.7% vs 46.7%) compared with case-matched patients not receiving continuous NMB (32).…”
Section: Resultsmentioning
confidence: 99%
“…The small case-control study performed in a low-resource setting (LRS) showed lower mean OI and lower mortality (13.7% vs 46.7%) compared with case-matched patients not receiving continuous NMB (32). However, a propensity score analysis of the Randomized Evaluation of Sedation Titration for Respiratory Failure trial (12) in patients with moderate-to-severe PARDS who received NMB for the entire duration of days 1 and 2 after initiation of invasive MV did not show significant differences in 90-day mortality, cognitive or functional impairment at hospital discharge or at 6 months post-PICU discharge (33). The authors did, however, observe a longer duration of MV with early NMB, even after stratifying and adjusting for patient characteristics associated with the use of early NMB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, a secondary analysis of the prospective Randomized Evaluation of Sedation Titration for Respiratory Failure study demonstrated no increased mortality. 24 Although these CNMB studies provide some insights regarding mortality risk, they cannot be generalized to infants with severe BPD.…”
Section: Discussionmentioning
confidence: 99%
“…If pathophysiologic derangements of sepsis are mechanistic drivers of the development and progression of comorbid conditions, then efforts to better prevent and treat sepsis may serve to not only decrease the burden of hospitalization and mortality due to sepsis but also decrease the downstream development of comorbid conditions. We must also consider the acute sequelae of sepsis and critical illness and its associated treatments, such as ICU-acquired weakness, mechanical ventilation, and neuromuscular blockade, because these are likely to affect patient outcomes.…”
Section: Discussionmentioning
confidence: 99%